DESENVOLVIMENTO DE TECNOLOGIA PARA MULHERES COM DEFICIÊNCIA VISUAL: ACESSIBILIDADE NA CADERNETA DA GESTANTE - Cassol, Rejane (2024)
Accessibility refers to the quality of something being accessible to all people, regardless of their physical, sensory, intellectual, or social conditions. Accessibility to information and health services during pregnancy is a right for all women, including those with visual impairments. The pregnant woman's handbook is a fundamental tool in this process. It is used as an effective communication channel between health professionals and the pregnant woman. This document also serves as a tool for empowering women, allowing them to monitor their progress and better understand their pregnancy. Objectives: To learn about the challenges faced by visually impaired women during the pregnancy-puerperium cycle in the health context; To describe the methodological steps for building a prototype of an inclusive pregnant woman's booklet using Design Thinking. Methodological approach: Firstly, a literature review was carried out in order to recognize the gaps in the subject studied, as well as the theoretical conceptual path of visual impairment. The second stage was characterized by descriptive-exploratory research with a qualitative approach. These two initial stages formed the basis for the third stage, called the development of the technological product, which describes the development of the adaptation of the pregnancy booklet for people with visual impairments using Design Thinking. Results: The main challenges related to health services encountered were the lack of accessibility in health services, the difficulty in communicating with health professionals, the scarcity of information adapted to their needs, and also the lack of adequate social support. The application of Design Thinking in the development of this product was fundamental to ensuring the inclusion of visually impaired women. By using this approach, we were able to listen directly to the women, understanding their specific needs and challenges. This collaborative process allowed them to actively participate in the construction of the booklet, resulting in a resolutive, effective and personalized product. In this way, Design Thinking not only promoted inclusion, but also ensured that the care proposals were truly aligned with the users' reality. Final Considerations: Applying the Design Thinking method, as it is a type of collaborative, problem-solving approach, enabled the creation of a prototype of a Pregnancy Handbook adapted to the reality of visually impaired women. This adaptation represents a step forward in promoting the inclusion and autonomy of visually impaired women, generating significant impacts on society by changing paradigms, demonstrating that it is possible to adapt resources and services to meet the needs of people with disabilities, promoting social inclusion. The adapted Pregnant Women's Handbook has high replicability potential and can be implemented in different regions and health services. The innovation lies in adapting the content and format of the booklet to make it accessible to visually impaired pregnant women. For the target audience (visually impaired people) this adaptation results in a significant impact, providing access to information, empowerment and autonomy, improved quality of prenatal care, risk reduction and social inclusion.